PENDIDIKAN AKHLAK DALAM AL-QUR’AN (Upaya Meningkatkan Akhlak Terpuji Dengan Nilai-Nilai Dalam Al-Quran) - Ishak, Ishak; Khairunnisa, Fitri; Nasution, Fatimah (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
This study aims to find out moral education in the Qur''an, as well as the efforts made to improve morals in accordance with the values ​​contained in the Qur'an. can increase commendable morals, namely by the presence of internal factors and external factors where these two factors are influenced by the quality of learning and the abilities of each student. Based on the conclusions of this study, there are efforts that can be made by teachers and families to improve the morals of their children, especially those who important role is the school environment and society. These efforts are introducing monotheism, giving advice, refracting noble morals, being a pleasant figure and setting a good example.